2016
DOI: 10.1186/s12985-016-0646-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and phylogenetic analysis of porcine epidemic diarrhea virus in central China based on the ORF3 gene and the S1 gene

Abstract: BackgroundPorcine epidemic diarrhea (PED) has increased in severity in China since 2010. To investigate further the infectivity, genetic diversity and molecular epidemiology of its causative agent, the porcine epidemic diarrhea virus (PEDV), we assessed 129 clinical samples, which were the intestinal tissue of piglets with severe diarrhea, from 17 cities in central China. Both the spike (S) glycoprotein (S1, 1–789 amino acids (aa)) and the full-length ORF3 gene of 21 representative field strains from 21 farms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The ORF3 protein exhibits a genetic variation among PEDVs. Sequence comparison of virulent and attenuated PEDV strains revealed that some of attenuation-related mutations are located in the ORF3 genes (Chen et al, 2010;Su et al, 2016), suggesting that ORF3 protein exhibits a genetic variation among PEDVs. In addition, ORF3, as the only accessory gene in PEDV, is thought to function as an ion channel and to influence virus production and virulence (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ORF3 protein exhibits a genetic variation among PEDVs. Sequence comparison of virulent and attenuated PEDV strains revealed that some of attenuation-related mutations are located in the ORF3 genes (Chen et al, 2010;Su et al, 2016), suggesting that ORF3 protein exhibits a genetic variation among PEDVs. In addition, ORF3, as the only accessory gene in PEDV, is thought to function as an ion channel and to influence virus production and virulence (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The S protein is the major envelope glycoprotein responsible for receptor binding, virus attachment, cell membrane fusion and entry [7]. M protein, the most abundant surface protein, is co-expressed with E protein to form pseudo-particles which results in interfering genic activity [8]. N protein is highly conserved and the epitopes may be important for induction of cell-mediated immunity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other isolates in 2016 in the Beijing area showed a closer relationship with previous isolates in Guangdong. This revealed that S genes accumulated variations faster based on inherent genetic characteristics or recombinant genes from other isolates [ 10 , 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%